Resolusi Konflik Sosial Keagamaan Masyarakat Pulau Raam Kota Sorong, Papua Barat - Muhammad Rusdi Rasyid; Umar Sulaiman; Rosdiana Rosdiana; Sudirman Sudirman (LPPM IAIN Sorong, 2021)
The harmony of the life of the Butonese and other ethnic groups was disturbed by the presence of Pelangi PAUD, the Pentecostal Church, and the Foreign Congregation on Raam Island. The purpose of this research is to describe the potential for community conflict in Raam Island, Sorong City by uncovering the factors that trigger the potential for conflict and finding alternative harmonization of the Raam Island community. Data were collected qualitatively through semi-structural in-depth interviews, non-participatory observation, and documentation. This research shows that First; The socio-religious conflict began when the management of the Pelangi PAUD Foundation broke a promise to involve Muslim teachers to teach early childhood students. Second; The construction of the Pentecostal Church which was deemed not in accordance with the existing regulations, the atmosphere became increasingly cloudy when the Church congregations were not local residents and were not known. Harmonization solutions can be done by strengthening the organizational functions of the FKUB to be improved both among the people of Raam Island and the government. Socialization of the Joint Regulation of the Minister of Religion and the Minister of Home Affairs concerning the Maintenance of Religious Harmony, Empowerment of Religious Harmony Forums, and the Establishment of Houses of Worship.